Regresi Religiusitas Terhadap Konsumerisme pada Mahasiwa UIN Raden Fatah Palembang - Sonia Ramadhan; Arma Yunis; Muhammad Daffa Dhiya’ulhaq; Rinol Sumantri; Heri Junaidi (CV. Era Digital Nusantara, 2025)
The purpose of the article is to analyze how the understanding of religiosity of UIN Raden Fatah Palembang students on consumption behavior (consumerism). This article discusses how the understanding and application of religion has an influence on individual behavior, in this case consumption behavior. This article proves that a good understanding and application of religion can have a positive impact on consumption behavior. Meanwhile, religiosity is found to have a negative influence on student consumerism, meaning that the higher the level of student religiosity, the lower the student consumerism. This study suggests that religiosity affects student consumption behavior by 1.3%, while the remaining 98.7% is influenced by other variables not explained in this study.